Impact of Social Media on HR Functions: A Review - Kaur, Tejbir; Zafar, Sayeeduz (Prabandhan: Indian Journal of Management, 2015)
Gone are the days when individual meetings were conducted for policy sharing and when HR people used to travel from one location to another, announcing new practices, promotions, and separations, but with the emergence of social media, a single tweet/Facebook update or a post on the Internet-based organization management system serves as a public notice for any type of organizational change, throwing a wrinkle in the corporate communication process. This article tries to explore the impact of social media on various HR functions like talent management, recruitment and selection, performance management, employer branding, and discusses various risks associated with it. This article might be useful for all concerned corporate leaders and managers who want to optimally utilize social media as a tool to implement policies and practices in their organizations.